Efficacy and safety of rituximab in children with steroid- and calcineurin inhibitor-dependent nephrotic syndrome: a systematic review of randomized controlled trials - Sharon, Sharon; Nadhifah, Nadhifah; Heriawan, Timotius Ivan; Rahmatika, Nadya; Zahara, Nadia Eva; Purnomo, Athaya Febriantyo; Lazarus, Gilbert (Indonesian Pediatric Society, 2024)
Background Efficacy of rituximab in the management of idiopathic nephrotic syndrome in children is well-established, however there is limited evidence of its efficacy in children with steroid- and calcineurin inhibitor-dependent nephrotic syndrome (CNI-SDNS). Objective To investigate the efficacy and safety of rituximab in children with CNI-SDNS. Methods We conducted a comprehensive search for relevant RCTs in PubMed, Scopus, Cochrane Central Register of Controlled Trials, and Google Scholar. Eligible RCTs were included, assessed for risk of bias using the Revised Cochrane risk-of-bias tool for randomized trials, and summarized narratively. Results A total of five RCTs (299 children) were included in the review. Rituximab was effective in maintaining remission and preventing relapse in pediatric CNI-SDNS patients, in a manner potentially superior to conventional therapy. Furthermore, rituximab successfully resulted in a higher rate of steroid and CNI withdrawal, along with prolonged drug-free period. However, the benefits of rituximab in children with focal segmental glomerulosclerosis (FSGS) remains equivocal. The drug was generally well-tolerated, both in the short-term and long-term, with a low incidence of adverse events and infusion reactions, typically of mild and reversible nature. Conclusion Rituximab appears to be effective and safe in treating children with CNI-SDNS, offering potential benefits in reducing dependence on steroids and CNIs. Larger trials comparing the effectiveness of rituximab specifically between children with minimal change disease (MCD) and FSGS are warranted to further validate and strengthen our findings.